Ag2ZnSnS4/Mo-mesh photoelectrode prepared by electroplating for efficient photoelectrochemical hydrogen generation. Issue 4 (3rd January 2019) - Liang, Xizhuang; Wang, Peng; Huang, Baibiao; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying
Abstract : Ag2 ZnSnS4 /Mo-mesh photoanode was prepared by a simple electrodeposition and in situ sulfurization method, which had lower onset potential and higher photocurrent density. Abstract : In this paper, n-type Ag2 ZnSnS4 (AZTS) thin film was prepared by a simple electrodeposition and in situ sulfurization method on Mo-mesh substrate. Pristine AZTS photoanode yielded a photocurrent density of 4.0 mA cm −2 at 0.6 V vs. RHE. In order to improve the stability of Ag2 ZnSnS4 photoanode, TiO2 offering more protection against the photo corrosion was deposited through an atomic layer deposition (ALD) process. IPCE measurements were used to evaluate solar energy utilization efficiencies of AZTS and TiO2 /AZTS photoanodes, which showed 25% and 20% IPCE (510–530 nm) in water splitting reaction, respectively. The analysis of gas yield determined that the faradaic efficiency during the H2 evolution process was over 90%. Furthermore, the reasons for the high photoelectrochemical performance of AZTS/Mo-mesh and mechanism of PEC H2 evolution in system are discussed below.